ADAPTASI KLON-KLON BAWANG MERAH (Allium ascollonicum L.) DI PABEDILAN LOSARI – CIREBON - Sartono Putrasamedja (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2010)
The purpose of this experiment is to obtain clones of onion that can adapt well in Losar. Ten clones of hybrid onion that has been selected by two local varieties as compares were planted at low elevation of Losari Pabedilan in 16 m asl using Randomyzed Completely Block Design, from June - September 2007. The results showed that clone no. 10 is a clone of onion that can be adapted well and have the appearance of new growth and results in high-Losari Pabedilan Cirebon, are consistent with the expectations of the users who may ultimately be developed commercially. Keywords : red onion, clone, adaptation, growth, yield